Westonci.ca connects you with experts who provide insightful answers to your questions. Join us today and start learning! Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.

What is the solution to 8x minus 3(2x minus 4) = 3(x minus 6)

Sagot :

Answer:

x = 30.

Step-by-step explanation:

8x - 3(2x - 4) = 3(x - 6)

8x - 3*2x + - 3*-4 = 3*x + 3 * -6

8x - 6x + 12 = 3x - 18

2x + 12 = 3x - 18

2x - 3x  + 12 = 3x - 3x - 18

-x + 12 = -18

-x + 12 - 12 = -18 - 12

-x = -33

-x/-1 = -30/-1

x = 30.

Answer:

[tex]x=30[/tex]

Step-by-step explanation:

[tex]8x-3\left(2x-4\right)=3\left(x-6\right)[/tex]

First, we will expand [tex]-3\left(2x-4\right)[/tex] by applying the distributive property:

[tex]-3\times \:2x-\left(-3\right)\times \:4[/tex]

** [tex]-\left(-a\right)=a[/tex]

[tex]-6x+12[/tex]

[tex]8x-6x+12=3\left(x-6\right)[/tex]

Expand, [tex]3\left(x-6\right):[/tex]

[tex]3x-3\times \:6[/tex]

[tex]3x-18[/tex]

[tex]2x+12=3x-18[/tex]

Subtract 12 from both sides:

[tex]2x+12-12=3x-18-12[/tex]

[tex]2x=3x-30[/tex]

Subtract 3x from both sides:

[tex]2x-3x=3x-30-3x[/tex]

[tex]-x=-30[/tex]

Divide both sides by -1:

[tex]\frac{-x}{-1}=\frac{-30}{-1}[/tex]

[tex]x=30[/tex]

________________________